Genetic background determines synaptic phenotypes in Arid1b-mutant mice - Kim, Hyosang; Kim, Eunjoon (Frontiers in Psychiatry, 2024)
ARID1B, a chromatin remodeler, is strongly implicated in autism spectrum disorders (ASD). Two previous studies on Arid1b-mutant mice with the same exon 5 deletion in different genetic backgrounds revealed distinct synaptic phenotypes underlying the behavioral abnormalities: The first paper reported decreased inhibitory synaptic transmission in layer 5 pyramidal neurons in the medial prefrontal cortex (mPFC) region of the heterozygous Arid1b-mutant (Arid1b +/-) brain without changes in excitatory synaptic transmission. In the second paper, in contrast, we did not observe any inhibitory synaptic change in layer 5 mPFC pyramidal neurons, but instead saw decreased excitatory synaptic transmission in layer 2/3 mPFC pyramidal neurons without any inhibitory synaptic change. In the present report, we show that when we changed the genetic background of Arid1b +/-mice from C57BL/6N to C57BL/6J, to mimic the mutant mice of the first paper, we observed both the decreased inhibitory synaptic transmission in layer 5 mPFC pyramidal neurons reported in the first paper, and the decreased excitatory synaptic transmission in mPFC layer 2/3 pyramidal neurons reported in the second paper. These results suggest that genetic background can be a key determinant of the inhibitory synaptic phenotype in Arid1bmutant mice while having minimal effects on the excitatory synaptic phenotype.